PERSEPSI MASYARAKAT TERHADAP KUALITAS PELAYANAN KESEHATAN DI PUSKESMAS TELUK DALAM KECAMATAN TELUK DALAM KABUPATEN NIAS SELATAN - MANGARAJA, GUSTRIANA; HUTAHAEAN, MARLAN; SINAGA, DEARLINA (JURNAL ILMIAH MAKSITEK, 2021)
STH infection is an environmental-based disease that is still a health problem for Indonesian people who are transmitted through land. This infection generally attacks elementary school age children. This study aims to determine the relationship of STH infection with the level of hygiene in 105296 elementary school students Percut Sei Tuan. This research is analytic descriptive with cross sectional approach. The sampling technique is done by a total sampling method with a total sample of 190 students. Data processed with chi square test. The results showed that there was a relationship between STH infection and the level of hygiene in 105296 elementary school students Percut Sei Tuan. With a lack of hygiene level in the Public Elementary School 105296 Percut Sei Tuan as many as 50 people. There is a relationship between STH infection and the level of hygiene in 105296 elementary school students Percut Sei Tuan.